Measures of Adipose Tissue Redistribution and Atherosclerotic Coronary Plaque in HIV. Issue 4 (21st February 2020) - Bogorodskaya, Milana; Fitch, Kathleen V.; Lu, Michael; Torriani, Martin; Zanni, Markella V.; Looby, Sara E.; Iyengar, Sanjna; Triant, Virginia A.; Grinspoon, Steven K.; Srinivasa, Suman; Lo, Janet
Abstract : Objective: People with HIV (PWH) who are well treated on antiretroviral therapy remain at increased risk for body composition changes, including increased visceral adipose tissue (VAT) and reduced subcutaneous adipose tissue (SAT), as well as increased cardiovascular disease (CVD). The relationship between adipose compartments and coronary disease is not well understood among PWH. Methods: A total of 148 PWH and 68 uninfected individuals without CVD were well phenotyped for VAT and SAT via single‐section abdominal computed tomography (CT) at L4. Coronary artery calcium (CAC) score was assessed by noncontrast cardiac CT and coronary plaque composition by coronary CT angiography. Results: Increased VAT was significantly related to increased presence of plaque (OR, 1.55 per 100 cm 2 ; P  = 0.008) and CAC > 0 (OR, 1.56 per 100 cm 2 ; P  = 0.006) in the HIV group. In contrast, increased SAT was related to reduced presence of plaque (OR, 0.79 per 100 cm 2 ; P  = 0.057) and reduced CAC > 0 (OR, 0.69 per 100 cm 2, P  = 0.007) among PWH. The VAT to SAT ratio showed a strong relationship to overall presence of calcified plaque (OR, 3.30; P  = 0.03) and CAC > 0 (OR, 3.57; P  < 0.001) in the HIV group. VAT and waist to hip ratio, but not SAT, were strong predictors of plaque in the uninfected group. BMI did not relate in either group. Conclusions: Fat redistribution phenotyping by simultaneous quantification of VAT and SAT as independent measures could help identify those PWH at higher risk for CVD.